Toy story: joke book - Bazaldua, Barbara (New York : A Golden Book, 1996)
Join Woody, Buzz, Hamm, and the rest of the Toy Story crew as they share their favorite jokes, riddles, and tounge twisters in this laugh-packed book.
Keywords: Toys--Fiction; Children stories